Does supporting passenger railways reduce road traffic externalities? - Rafael Lalive; Simon Luechinger; Armin Schmutzler (University of Zurich, Department of Economics, 2013)
Many governments subsidize regional rail service as an alternative to road traffic. This paper assesses whether increases in service frequency reduce road traffic externalities. We exploit differences in service frequency growth by procurement mode following a railway reform in Germany to address endogeneity of service growth. Increases in service frequency reduce the number of severe road traffic accidents, carbon monoxide, nitrogen monoxide, nitrogen dioxide pollution and infant mortality. Placebo regressions with sulfur dioxide and ozone yield no effect. Service frequency growth between 1994 and 2004 improves environmental quality by an amount that is worth approximately 28-40 % of total subsidies. An analysis of household behavior shows that the effects of railway services on outcome variables are driven by substitution from road to rail.
Keywords: Q53; R41; R48; 330; railways; pollution; procurement; accidents; Schienenpersonennahverkehr; Verkehrssubvention; Wirkungsanalyse; Nachhaltige Mobilität; Straßenpersonenverkehr; Externer Effekt; Schätzung; Deutschland